Mediterranean diet: a precious tool for fighting inflammatory diseases - Catarino, Marcelo D. (2015)
Epidemiological studies indicate that populations who consume foods rich in specific polyphenols have lower incidence of inflammatory diseases. In turn, Mediterranean diet, claimed for its several health benefits, provides a wide range of foods which are particularly enriched sources of polyphenols, some of which known for their anti-inflammatory properties. In this context, various herbs, vegetables and fruits, as well as fruit derivative products, such as wine and virgin olive oil, are believed to have an important role preventing and/or ameliorating inflammatory conditions through diet. Additionally, they are strong candidates for anti-inflammatory drugs. In general, the anti-inflammatory properties of polyphenols involve the modulation of pro-inflammatory gene expression including cyclooxygenase, lipoxygenase, nitric oxide synthases and several pivotal cytokines such as TNF-α, interleukin-1 (IL-1) and interleukin-6 (IL-6), mainly by acting through nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling. Since inflammation is a phenomenon present in many chronic diseases including cancer, diabetes, obesity, and cardiovascular disease, the modulation of the aforementioned markers by polyphenols may positively contribute for the prevention and/or amelioration of these diseases. The present chapter focus various edible Mediterranean typical foods known for their anti-inflammatory properties, as well as the main pheno-lic constituents associated to the protection process and their underlying mechanisms of action.